Factors contributing to increased physical activity among young people of working age - Dorohov S.I.; Samigullina G.Z.; Grebennikov A.I.; Malinin A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify motivational factors for involving able-bodied young people in physical education. Methods and structure of the study. Based on a survey of 920 students, three key motivational blocks were identified: self-affirmation (especially significant for physically active young men), health (a universal priority) and self-improvement (important for young women). Results and conclusions. It has been established that 61.2 % of physically active young men and 60.2 % of young women consider health improvement to be their main motivation, while competitive motives are significant for 52.3 % of active young men compared to 26.3 % of physically inactive young men. The authors propose a differentiated approach to motivating able-bodied young people, taking into account gender characteristics and levels of physical activity, with an emphasis on competitive programs for boys and fitness activities for young women.